Copyright Infringement in the Distribution of Exclusive Content on Instagram - Halawane, Nitha; Akyuwen, Rory Jeff; Narwadan, Theresia Nolda Agnes (TATOHI: Jurnal Ilmu Hukum, 2025)
Introduction: The advancement of digital technology has led to the widespread distribution of exclusive content on Instagram, including copyright-protected works such as photos and videos. The unauthorized dissemination of such content raises legal issues concerning copyright protection and dispute resolution mechanisms in Indonesia.Purposes of the Research: The purpose of this study is to understand the protection of copyright in relation to the dissemination of exclusive content on Instagram and to identify the dispute resolution mechanisms for such unauthorized distribution.Methods of the Research: This research employs a normative juridical method using statutory and conceptual approaches, based on primary and secondary legal materials. Data collection is conducted through library research, and analysis is carried out descriptively to interpret and systematically organize legal documents in a rational and scholarly manner.Findings of the Research: The results of this studi are paid exclusive content on Instagram is protected under Law Number 28 of 2014 on Copyright, which grants creators both moral and economic rights. Unauthorized distribution, such as by the TikTok account @joingrupexclusive, constitutes a copyright infringement. While Instagram provides reporting mechanisms, the primary responsibility to address violations lies with the rights holder. Disputes may be resolved through negotiation, mediation, conciliation, arbitration (if an agreement exists), or court proceedings. If informal methods fail, litigation in the Commercial Court may be pursued in accordance with Articles 100–101 of the Copyright Law, requiring proof of copyright ownership to impose sanctions, including damages.